Evaluasi dan Perbaikan Rancangan Antarmuka Pengguna Situs Web Eventmalang Menggunakan Pendekatan Human Centered Design - Rahadian Irwandana; Admaja Dwi Herlambang; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
EVENTMALANG website is a media for reporting information about event performances in Malang, Batu, and its surroundings which is located at www.eventmalang.net. This study discusses how to increase the level of usability website using the WEBUSE questionnaire which has 4 categories of Content,vOrganization andvReadability, Navigationvand Links, UservInterface Design and Performancevand Effectiveness which are given to 30 respondents with purposive sampling technique. Solution design making applies the Human Centered Design (HCD) approach and then evaluates the solution design again. The results of the solution design evaluation showed the highest increase in the category of User Interface Design that experienced an increase of 0.103. Followed by Navigation and Links an increase of 0.086. Content, Organization and Readability has increased by 0.065, and Performance and Effectiveness has increased by 0.055.